Digital Administration Management In Improving Efficiency At Alhidayah Kalisari Islamic Boarding School - Ahmad sofil ghifari; Iis Maisaroh; Muhtarom Muhtarom (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to describe the effectiveness of implementing digital administration through the Smart Hida (Cashless System) at the Alhidayah Kalisari Islamic Boarding School.  feature expansion, a qualitative method with a participatory case study approach. Data collection was carried out from April 16 to 24, 2026, through observation and in-depth interviews with the central treasurer and administrative members. The results showed that the digitalization of financial transactions had a significant positive impact. The cashless system effectively minimizes student indiscipline, as the absence of physical cash eliminates their motivation to buy snacks outside the boarding school without permission. For parents, this system provides transparency and daily control over their children's expenses, eliminating the need to physically visit the school to pay fees. From the management side, the manual administrative burden previously done in physical books is replaced by an automatic database and a top-up system. Furthermore, the integration of 30 internal merchants with a mutually agreed maintenance fee system creates a sustainable business ecosystem. However, this implementation faces challenges regarding users' digital literacy, so feature expansion needs to be done gradually.